Molecular Docking and Molecular Dynamic Simulation on the Interaction of Saffron’s Active Compunds with HER-2 Protein - Adelina, Rosa; Maharani, Dila Aulia; Octaviani, Putri; Putra, Sendi Handika (Indonesian Journal of Cancer Chemoprevention, 2023)
Human epidermal growth factor receptor-2 (HER-2) is an essential oncogene in breast cancer. HER-2 causes 25% of breast cancer, and this type of cancer tends to grow and spread faster than others but had a good response to HER-2 targeted therapy. This study aims to analyze chemical compounds in saffron plants (Crocus sativus) that potential to breast anticancer activity by inhibiting HER-2 receptor (PDB ID: 3RCD). The study employed in silico research such as molecular docking using AutoDock Tools software, and visualization with Biovia Discovery Studio. In addition, molecular dynamic simulation was conducted using GROMACS software, with visualization performed using Grace. The molecular docking results showed that Crocetin has a lower binding energy value of -8.37 kcal/mol compared to Herceptin, which is -7.11 kcal/mol and the lowest energy among Saffron bioactive compounds. These results indicated that the affinity of Crocetin in binding to HER-2 receptor is better than Herceptin. The molecular interactions were hydrogen, hydrophobic, electrostatic, and unfavorable bonds. The MD results showed that the RMSD value meets the 0.2-0.5 nm stability requirements. According to the data analysis, Herceptin appears to have a more stable RMSF value when compares to Crocetin. The Rg graph of both complexes showed stability until the end of the simulation. The H-bond results show that the Herceptin complex has more hydrogen bonds than the Crocetin complex. These results showed that the chemical components of saffron plants have the potential as breast anticancers by inhibiting the HER-2 receptor.Keywords: anticancer, Crocus sativus, HER-2 receptor, molecular docking, molecular dynamic.